A new species of the genus Corneriella from India supported by morphological and molecular data - Raj, K. N. Anil; Latha, K. P. Deepna; Sánchez-García, Marisol; Manimohan, Patinjareveettil (Phytotaxa, 2015)
Corneriella indica sp. nov. is described from Kerala State, India. Comprehensive description, photographs, and comparisons with phenetically similar species are provided. Maximum likelihood analysis conducted on a concatenated dataset comprising ITS, nLSU, nSSU and rpb2 of the Tricholomataceae supported the generic placement and species validity of C. indica. Conspicuous cheilocystidia, one of the defining features of the genus, are missing in C. indica but the lamella edges are still sterile and composed of projecting tramal hyphae with cystidioid terminal elements.